The Effect of Landscape Linguistics on Students’ Vocabulary - Liza Maulia; Yendra; Dian Noviani Syafar (Journal of Language Education (JoLE), 2023)
This research was motivated by the researcher's interest in the use of linguistics landscape in English at SMAN 10. This research aims to determine the effect of linguistics landscape on students' vocabulary. In this study, the researcher used quantitative research, with a sample of 100 students from grades 10, 11, and 12 of SMA N 10 Padang. The sampling technique in this study used the Random Sampling method. Data collection was carried out using a questionnaire with the Guttman Scale. The analytical method used in this study is a simple regression analysis method with the SPSS Version 22.0 application. Based on the research results, in general, Landscape Linguistics affects vocabulary, although there are still a small number of LL in SMA Negeri 10 Padang City that do not affect student vocabulary. The results of this study are not intended for all linguistics landscapes in public places because the LL test in this study was only in one school. Keywords: Effect Linguistics Landscape, Vocabulary